Brexit and Trump: Which Theory of Social Stasis and Social Change Copes Best With the New Populism? - Owuamalam, Chuma Kevin; Rubin, Mark; Spears, Russell (Frontiers in Psychology, 2022)
Why do voters seek to change the political landscape or to retain it? System justification theory (SJT) proposes that a separate system motive to preserve the existing order drives support for the status-quo, and that this motivation operates independently from personal and collective interests. But how does this explanation apply to recent populist shifts in the political order such as Brexit and the emergence of Donald Trump? While the system motive may seem useful in understanding why the usual progressives (Remain/Clinton voters) may want to stick with an established order, it seems insufficient to explain why the more conservative voters (Brexit/Trump voters) would want to upend the establishment. Thus, we compared SJT’s system motive explanation for the system attitudes of voters on both sides of the political divide to an alternative explanation drawn from the newer social identity model of system attitudes (SIMSA). According to SIMSA, the difficulty in explaining the system attitudes of Brexit/Trump and Remain/Clinton voters from SJT’s system motive standpoint can be resolved by focusing instead on the collective interests that both camps seek to satisfy with their votes. We examined these explanations in two studies conducted soon after Brexit (N = 313) and Trump’s election (N = 289) in 2016, with results providing more support for SIMSA than for SJT.